PROBLEMATIKA DAN SOLUSI PEMENUHAN PERLINDUNGAN HAK ANAK SEBAGAI TERSANGKA TINDAK PIDANA DI SATLANTAS POLRESTATA PARIAMAN - Laurensius Arliman S (Justicia Islamica, 2016)
Children as the nation's next generation is obliged to be protected. Kids in his life will not be separated from violence every day, it can be seen on the television news, news in print or electronic. It's very sad child protection are not met, because it is the same as destroying Indonesia in the future. Child protection can not be separated from the children as victims, children as witnesses, or bahakan child as a criminal suspect. This paper uses empirical juridical methods. This paper discusses how the fulfillment of children as perpetrators of the traffic in the Traffic Police of Padang Pariaman. There are problems that occur both from internal factors or external factors, but in this study presented also the solution of the existing problems. The conclusion of this paper expects that the future of child protection is more responsive, and all parties are willing to assist in the enforcement of child protection.